LAYANAN BIMBINGAN KELOMPOK TENTANG KEPERCAYAAN DIRI PESERTA DIDIK KELAS X SMA NEGERI 5 PONTIANAK - Fitriani Fitriani; M. Asrori; Luhur Wicaksono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractResearchers want to know the implementation of group guidance about student confidence. The research problem is "how is the group guidance about the confidence of students in class X SMA Negeri 5 Pontianak". The purpose of the study was to obtain information and clarity and describe group guidance about the confidence of students in class X SMA Negeri 5 Pontianak. Method used was descriptive quantitative approach in form survey. Population research was 24 students and 1 counselor. Data collection technique used was indirect communication of questionnaires and interviews. Data analysis technique used was percentage. Overall the implementation of group guidance on student confidence gained 54% category quite well. Characteristics of self-confidence of class X students SMA Negeri 5 Pontianak medium category, the results obtained are 40% medium category. The stage of forming a group guidance service on the students' confidence gained 51% quite good category. The transition phase of group guidance services on student confidence gained 63%, quite good category. The stage of group guidance service activities about the confidence of students gained 59% quite good category. The termination stage of group guidance services on the confidence of students gained 60% quite good category.Keywords: Group Guidance, Confidence